Assessment of intra-sample variability in HIV-1 DNA drug resistance genotyping. (29th May 2021) - Millière, Laurine; Bocket, Laurence; Tinez, Claire; Robineau, Olivier; Veyer, Nathalie; Wojciechowski, Fanny; Lambert, Valérie; Meybeck, Agnès; Huleux, Thomas; Ajana, Faiza; Hober, Didier; Alidjinou, Enagnon Kazali
Abstract: Background and objectives: HIV-1 drug resistance testing can be performed in proviral DNA. The non-homogenous distribution of viral variants in cells can impact the performance of this method. We assessed the variability of HIV-1 DNA genotyping results in the same blood sample using a next-generation sequencing (NGS) method. Methods: For each included patient, a blood sample from a single venipuncture was split into five 1 mL aliquots, which were independently tested in the same run. HIV-1 DNA was quantified in blood samples using real-time PCR, and NGS was performed with the Sentosa platform combined with the Sentosa SQ HIV genotyping Assay. Results: A total of 60 aliquots from 12 samples (12 patients) were tested. The median age was 45.50 years old, and all patients were treated with antiretrovirals. A significant variability can sometimes be observed in HIV-1 DNA quantification between aliquots from the same sample, with a coefficient of variation ranging from 23% to 89%. The analysis of resistance-associated mutations (RAMs) with a 20% cut-off found some discordances in RAMs profile between aliquots from the same sample for 5, 3 and 3 patients in the reverse transcriptase, protease and integrase genes, respectively. The analysis with a lower cut-off (10%) showed additional mutations, but did not improve the intra-sample concordance. Conclusions: There is an intra-sample variability in HIV-1 DNA resistance test results, and repetition may sometimes bring additional information, but the extent of its clinical impact still requires further investigation.